2008
DOI: 10.1590/s1516-35982008000700004
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de novilhas de corte submetidas a estratégias de suplementação em pastagens de aveia e azevém

Abstract: RESUMO -Avaliou-se o comportamento ingestivo de novilhas de corte recebendo suplemento em pastagem de aveia preta (Avena strigosa Schreb.) e azevém (Lolium multiflorum Lam.) sob lotação contínua. Como tratamentos, foram avaliadas quatro estratégias de suplementação: sem suplemento -animais em pastagem de aveia (AV) e azevém (AZ); crescente -animais em pastagem de AV e AZ recebendo níveis crescentes de suplemento (0,3; 0,6 e 0,9% do peso vivo -PV); fixo -animais em pastagem de AV e AZ recebendo nível fixo de su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
3
0
8
Order By: Relevance
“…Once forage supply was always above the double of the needs of the heifers and leaf blade supply did not present any differences (Table 2), bite rate remained unchanged among treatments. Moreover, supplementation also did not affect bite rate, which is in agreement with Bremm et al (2008), who did not find influence in bite rate with inclusion of increasing, decreasing and fixed levels of concentrate for lambs, so, the average, 57.1 bites/min, remained very close to the one found in this study. The number of feeding stations per minute presented correlation of -0.92 (P<0.0001) and -0.89 (P<0.0001) for time spent per feeding station and number of bites per feeding station, respectively, and the correlation between the latter two was 0.94 (P<0.0001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Once forage supply was always above the double of the needs of the heifers and leaf blade supply did not present any differences (Table 2), bite rate remained unchanged among treatments. Moreover, supplementation also did not affect bite rate, which is in agreement with Bremm et al (2008), who did not find influence in bite rate with inclusion of increasing, decreasing and fixed levels of concentrate for lambs, so, the average, 57.1 bites/min, remained very close to the one found in this study. The number of feeding stations per minute presented correlation of -0.92 (P<0.0001) and -0.89 (P<0.0001) for time spent per feeding station and number of bites per feeding station, respectively, and the correlation between the latter two was 0.94 (P<0.0001).…”
Section: Resultssupporting
confidence: 92%
“…Because forage mass was similar between all periods and leaf blade supply and the leaf:stem ratio presented a small variation in the last period in relation to the first period of evaluation, grazing time was constant, especially because there were no factors limiting pasture intake ( The grazing time in different periods was not influenced when increasing and decreasing levels of concentrate were offered to the heifers; however, grazing time varied for nonsupplemented animals and the ones which were fed fixed supplementation (Bremm et al, 2008). Those authors also conclude that the ingestive behavior of beef heifers grazing oat and ryegrass varied according to supplementation strategies and characteristics of pasture.…”
Section: Resultsmentioning
confidence: 99%
“…Hodgson (1985) and Bremm et al (2008) have likewise confirmed that, saying that the mass contained in the mouthful is the most important variable in determining intake by grazing animals; yet, the same was not observed in this study, since the mouthful mass was not correlated with any of the intake variables.…”
Section: Resultssupporting
confidence: 65%
“…The collection of climate data was performed simultaneously with the collection of behavioral data, every hour from 7 a.m. to 6 p.m.. For the evaluation of environments, the black globe-humidity index (BGHI) proposed by Buffington (1981) was used, and it was calculated the radiant thermal load index (RTL) proposed by Esmay (1979): BGHI = Bt + 0,36 Tdp + 41,5 where: Bt = black globe temperature (º C); Tdp = dew-point temperature (° C). RTL = σ T mr 4 , W/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the availability of forage (Table 1), it was made an assessment before the entry of the animals by using the double sampling methodology proposed by Wilm et al (1944) and Bremm et al (2008) and the bromatological analyses (dry matter, crude protein and neutral detergent fiber) were performed according to the methodology described by Silva (1999).…”
Section: Methodsmentioning
confidence: 99%